Brain volume is a better biomarker of outcomes in ischemic stroke compared to brain atrophy - Alhadid, Kenda; Regenhardt, Robert W.; Rost, Natalia S.; Schirmer, Markus D. (Frontiers in Stroke, 2024)
Objective This study aimed to determine whether brain volume at the time of ischemic stroke injury is a better biomarker for predicting functional outcomes than brain atrophy. Background Brain parenchymal fraction (BPF) has been used as a surrogate measure of global brain atrophy and a neuroimaging biomarker of brain reserve in studies evaluating clinical outcomes after brain injury. Brain volume itself is affected by natural aging, cardiovascular risk factors, and biological sex, among other factors. Recent studies have shown that brain volume at the time of injury can influence functional outcomes, with larger brain volumes being associated with better outcomes. Methods Acute ischemic stroke cases at a single center between 2003 and 2011, with neuroimaging obtained within 48 h of presentation were eligible for the study. Functional outcomes represented by the modified Rankin Scale (mRS) score at 90 days post-admission (mRS score ≤ 2 deemed a favorable outcome) were obtained through patient interviews or per chart review. Deep learning–enabled automated segmentation pipelines were used to calculate brain volume, intracranial volume, and BPF on the acute neuroimaging data. Patient outcomes were modeled through logistic regressions, and a model comparison was conducted using the Bayes information criterion (BIC). Results A total of 467 patients with arterial ischemic stroke were included in the analysis, with a median age of 65.8 years and 65.3% of the participants being male. In both models, age and a larger stroke lesion volume were associated with worse functional outcomes. Higher BPF and a larger brain volume were associated with favorable functional outcomes; however, a comparison of both models suggested that the brain volume model (BIC = 501) better explains the data than the BPF model (BIC = 511). Conclusion The extent of global brain atrophy (and its surrogate biomarker BPF) has been regarded as an important biomarker for predicting functional post-stroke outcomes and resilience to acute injury. In this study, we demonstrate that a higher global brain volume at the time of injury better explains favorable functional outcomes, which can be directly measured in a clinical setting.